The Recovery and Reuse of a MKII Fairey Barracuda from the Solent, Hampshire - Byford-Bates, Alistair (The international journal of nautical archaeology, 2024)
This paper reports on the archaeological recording and recovery of a MK II Fairey Barracuda from the Solent, Hampshire, off the south coast of England. As its location precluded the aircraft being left in situ, the decision was made to recover the aircraft. Despite adverse visibility, and a significant amount of overburden, the extant remains of the aircraft were successfully recovered and delivered to the Fleet Air Arm Museum for conservation, as part of an ongoing project to rebuild an example of a Fairey Barracuda. In being recovered for reuse and exhibition some of the Barracuda’s value to the wider community changed from that of a lost military aircraft to that of an historic object, drawing out the social history around it, and giving insights into military aircraft construction during the World War II.